Effect of Problem Based Learning Model Based on Roundhouse Diagram on Students' Problem Solving Ability SMA Negeri 1 Gondangwetan Ecosystem Material Class X - Nur Lindah Toyyibah; Arga Triyandana; Nur Lina Safitri (Universitas Nahdlatul Ulama Pasuruan, 2024)
This research was motivated by the low problem solving abilities of students regarding biology learning. This research aims to determine the effect of the problem based learning model based on roundhouse diagrams on students' problem solving abilities in class X ecosystem material at SMA Negeri 1 Gondangwetan for the academic year 2023/2024. This research is a quasi-experimental research using a non-equivalent control group design with a purposive sampling technique. For the research population, all students of class X SMA Negeri 1 Gondangwetan are 11 classes and the research sample consists of 2 classes, namely class class X-1 as a control class with a total of 35 students each. The research instrument is a description test. The data analysis technique uses a data requirements test with the SPSS version 25.0 for Windows program. Based on hypothesis testing using the t-test or independent sample test at a significance level (α) = 0.05, it shows that there is a significant influence of the problem based learning model on students' problem solving abilities. Thus, it can be concluded that there is a positive influence of the problem based learning model on students' problem solving abilities in class X ecosystem material at SMA Negeri 1 Gondangwetan for the academic year 2023/2024.